The Effects on Sick Leave of Changes in the Sickness Insurance System - Henrekson, Magnus; Persson, Mats (Journal of Labor Economics, 2004)
To get a more complete picture of how labor supply is affected by economic incentives, the effects on absenteeism should be taken into account. In particular, absenteeism due to sick leave can be considerable. We examine whether the level of sick leave compensation affects sick leave behavior. Using long time series data (1955–99) for Sweden with numerous changes of the compensation level, we generally find strong effects. Reforms implying more generous compensation for sick leave tend to be associated with permanent increases in sick leave, and vice versa. These findings are reinforced in a panel study covering the 1983–91 period.